Is the South African leech Barbronia gwalagwalensis Westergren & Siddall, 2004 (Hirudinida: Erpobdelliformes: Salifidae) a Paleotropical species? - Klass, Anna L.; Kondakov, Alexander V.; Vikhrev, Ilya V.; Bespalaya, Yulia V.; Lunn, Zau; Chan, Nyein; Gofarov, Mikhail Y.; Bolotov, Ivan N. (Zootaxa, 2021)
The freshwater leech family Salifidae Johansson has a Paleotropical range, with a hotspot of species richness in the Oriental Region, and a few species endemic to Africa, Madagascar, and Reunion. Barbronia gwalagwalensis Westergren & Siddall, 2004 was thought to be a characteristic example of the latter group being a lineage endemic to South Africa. However, we found that this species also occurs in Asia (Myanmar and Korea). Our time-calibrated phylogeny based on the mitochondrial cytochrome c oxidase subunit I (COI) gene reveals that the split between the African and Asian populations of this species occurred in the mid-Pleistocene, approximately 1.3 Ma ago (95% HPD 0.7-2.1 Ma). The statistical biogeographic modeling indicates that a B. gwalagwalensis population in South Africa most likely originated due a long-distance dispersal event with a subsequent vicariance (probability = 88.9%). A Late Quaternary range extension towards South Africa is known to occur in some other freshwater taxa (e.g. the freshwater mussel Unio caffer Krauss species group), which agrees with our hypothesis on the ancient origin of the South African B. gwalagwalensis population. Conversely, we can assume that the African population of this species was recently introduced from Asia. If so, the high levels of genetic divergence between African and Asian populations could be a part of a more general phylogeographic pattern historically originated within the Asian subcontinent due to the isolation by orographic or marine barriers. These two alternative hypotheses need further research efforts, i.e. sampling and sequencing of other Barbronia taxa, the ranges of which are situated between South Africa and Southeast Asia, as well as of topotypes of B. weberi (Blanchard, 1897) from Indonesia. Finally, our results highlight that the salifid genus Barbronia Johansson originated in the Oriental Region and that these leeches share both recently and historically high potential for long-distance dispersal events.